A 3D meshless radial basis reproducing kernel particle model for elastoplastic analysis of temperature-dependent FG plates resting on Winkler/Pasternak foundation. (November 2022) - Vaghefi, Reza; Karimzadeh, Ali
Highlights: 3D thermo-elastoplastic bending response of temperature-dependent FG plates on Winkler/Pasternak foundation is presented. A truly meshless approach based on the radial basis reproducing kernel particle method (RRKPM) is developed. Detailed parametric studies are performed on the scaling factor, shape parameter and node distribution. The stability and accuracy of the results are confirmed by analyzing several numerical examples. Different material gradients, elastic foundation parameters, thickness ratios, and boundary conditions are considered. Abstract: For the first time, a three-dimensional (3D) meshless approach based on the radial basis reproducing kernel particle method (RRKPM) is developed to scrutinize the nonlinear thermo-elastoplastic bending response of temperature-dependent functionally graded (FG) plates resting on Winkler/Pasternak foundation under a combination of mechanical and thermal loads. The modified rule of mixtures is employed to locally evaluate the effective temperature-dependent parameters of the functionally graded material (FGM). To describe the plastic behavior of the FG plate, the von Mises yield criterion, isotropic strain hardening, and the Prandtl-Reuss flow rule are adapted. To demonstrate the accuracy and efficiency of the present method, the outcomes are compared with other existing numerical and analytical results, which shows an excellent agreement. Detailed studies have been conducted on the scaling factor, shape parameter and nodal distribution for finding their desired values. Furthermore, the effect of significant parameters such as material gradient, elastic foundation parameters, thickness ratio, and boundary conditions on the bending response of FG plates has been investigated.